Concentration and distribution characteristics of rare earth elements lanthanum in forages under different dressing methods - JIANG Zhao-wei; WENG Bo-qi; HUANG Yuan-fang; HUANG Yi-bin; YING Zhao-yang (浙江大学学报. 农业与生命科学版)
The pot experiment was conducted to analyze the concentration and distribution characteristics of rare earth elements (REEs) lanthanum (La) in forages upon the foliage and soil dressing the La. The results show that the concentration of La in each part of forage plant increased with the increase of La application rate. The application of La by foliage dressing evidently enhanced the concentration of La in stems and leaves of forages. Compared with the control (non application of La), the concentration of La was increased by 110%-135% in the leaf and by 42%-140% in the stem of Gramineae grass Digitaria smutsii. Compared with the control, the concentration of La was increased by 37%-82% in the leaf and by 25%-45% in the stem of leguminous grass Chamaecrista rotundifolia. And at the same La application rate level, the concentration of La in stems and leaves was evidently higher by foliage dressing than that by soil dressing. The concentration of La in each part of forage plant with soil dressing was evidently different from that in the control only when the concentration of La application was high. At the same La application rate level, the concentration of La in root was lower by foliage dressing than that by soil dressing, but the difference was not evident. With the increase of La application rate, the concentration of La in pods of C. rotundifolia increased, but there was no evident difference between foliage dressing and soil dressing, each treatment and the control. By both foliage dressing and soil dressing, the order of concentration of La in D. smutsii plant was root > leaf > stem, while, that in C. rotundifolia plant was root≫ stem > leaf > pod.